2019
DOI: 10.1016/j.jad.2018.12.043
|View full text |Cite|
|
Sign up to set email alerts
|

Anxiety, depression, loneliness and social network in the elderly: Longitudinal associations from The Irish Longitudinal Study on Ageing (TILDA)

Abstract: Background: Social network, loneliness, generalized anxiety disorder (GAD) and major depression disorder (MDD) are interrelated. However, as the directions of these associations are still unclear, we examined them prospectively using community-based data. Methods: Data on 5066 adults aged ≥ 50 years from the Irish Longitudinal Study on Ageing (TILDA) were analyzed. Loneliness was assessed through the UCLA Loneliness Scale. Social integration was measured using the Berkman-Syme Social Network Index. MDD and GAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
227
2
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 323 publications
(267 citation statements)
references
References 46 publications
27
227
2
11
Order By: Relevance
“…29 Furthermore, depression can lead to low physical activity, while loneliness is known to be highly prevalent among older people with depression. 30,31 We also adjusted for setting (ie, rural or urban) as it is known that older people living in cities are often less physical active, 32 while urban living may influence loneliness. [33][34][35] Finally, we adjusted for household size (1, 2, and 3 or more) and social cohesion in the community to assess the independent effect of loneliness regardless of social ties.…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Furthermore, depression can lead to low physical activity, while loneliness is known to be highly prevalent among older people with depression. 30,31 We also adjusted for setting (ie, rural or urban) as it is known that older people living in cities are often less physical active, 32 while urban living may influence loneliness. [33][34][35] Finally, we adjusted for household size (1, 2, and 3 or more) and social cohesion in the community to assess the independent effect of loneliness regardless of social ties.…”
Section: Key Pointsmentioning
confidence: 99%
“…Health conditions (ie, chronic physical conditions, depression) were also adjusted for as poor health may limit the capacity for being physically active and induce loneliness . Furthermore, depression can lead to low physical activity, while loneliness is known to be highly prevalent among older people with depression . We also adjusted for setting (ie, rural or urban) as it is known that older people living in cities are often less physical active, while urban living may influence loneliness .…”
Section: Introductionmentioning
confidence: 99%
“…Rather, isolation 7 increased hyperactivity and exploration, findings that have been similarly observed in both sexes following earlylife isolation. In human populations, social isolation and loneliness correlate with cognitive decline, depression, and anxiety (Cacioppo et al, 2006;Domènech-Abella et al, 2019). Understanding the behavioral impacts of latelife isolation is especially relevant given the current self-isolation recommendations, particularly for females whose are more likely than males to live alone.…”
Section: Discussionmentioning
confidence: 99%
“…Experience of loneliness and perceived social isolation can also play an important role as factors of depression and anxiety in the elderly. A recent study conducted with older adults found a longitudinal and bidirectional association between experiencing loneliness and higher risk for major depression disorder (MDD) and generalized anxiety disorder (GAD) two years later(77). In the same study, perceived social isolation was also found independently associated with MDD and GAD.…”
mentioning
confidence: 84%